DOP74 Efficacy of ustekinumab in perianal Crohn's disease: the BioLAP multi-centre observational study. (25th January 2019) - Biron, C; Seksik, P; Nachury, M; Bouhnik, Y; Amiot, A; Viennot, S; Serrero, M; Fumery, M; Allez, M; Siproudhis, L; Buisson, A; Pineton de Chambrun, G; et al.
Abstract: Background: New therapeutic options for Crohn's disease (CD) patients with perianal lesions failing anti-tumour necrosis factor (TNF) therapy are needed. To date, no dedicated study with a large sample has evaluated the efficacy of ustekinumab on perianal CD (pCD). We assessed the efficacy of ustekinumab in pCD in a national multi-centre cohort and the predictive factors of success of the biological agent. Methods: We conducted a French multi-centre, and observational study (Bio-LAP) including all patients with either active or inactive pCD (but with history of fistulizing and drained perianal lesion over the past 10 years) who received ustekinumab. In patients with active pCD at treatment initiation, the success of the biological agent was defined by clinical recovery at 6 months of treatment assessed by physician's appreciation without using additional medical or surgical treatment for perianal lesions. In patients with inactive pCD at treatment initiation, clinical recurrence of pCD was defined by the occurrence of perianal lesions and/or need of medical or surgical treatment. Results: In total, 207 patients were screened. There were 75 (36.2%) males, the mean age at inclusion was 37.7 years, the mean BMI was 22 and the mean duration from CD diagnosis to initiation of treatment was 14.3 years. Of 207 (99%) patients, 205 have had at least 1 anti-TNF agent and a total of 197/207 (95.2%) patients had been exposed to thiopurine and/or methotrexate. Fifty-eight (28%) patients had previous exposure to vedolizumab. The mean number of prior perianal surgery was 2.8. The mean follow-up time was 66 weeks. Of 207(27%) patients, 56 discontinued therapy after a mean time of 363 days. In patients with active pCD at initiation, 88/148 (59.5%) patients had setons at initiation of therapy and ustekinumab success was reached in 56/148 (37.8%) patients. Among patients with setons at initiation, 29/88 (33%) patients had a successful seton ablation during follow-up. In multi-variate analysis, the only factor associated with treatment success was the absence of ustekinumab optimisation (OR 2.52; 95% CI 1.15–5.56; p = 0.01). Concomitant treatments (immunosuppressors and antibiotics), prior drainage or number of anti-TNF or prior biological agents were not predictors of success. In patients with inactive pCD at initiation, the mean follow-up time was 86 weeks, perianal disease recurred in 13/59 (22%) patients and 8/59 (13.6%) patients needed medical and/or surgical treatment for perianal disease. Mean time to recurrence was 25 weeks. Conclusions: Ustekinumab appears as a potential effective therapeutic option in perianal refractory CD. Further studies are needed to precise the role of ustekinumab in relation to other biological therapies for the management of refractory pCD.